Effect of reducing agents on batter consistency and physical characteristics of bread from sorghum flour - Fort, Emily L. (Kansas State University, 2016)
Sorghum is a vital cereal crop grown in many regions around the world. Tolerance to harsh climates and low moisture conditions are unique traits making sorghum an economical choice in an era of global water scarcity. In recent years, sorghum has gained greater recognition as a gluten-free grain and is a safe alternative for individuals suffering from gluten sensitivities or celiac disease. Still, the lack of gluten proteins does not allow sorghum to form a viscoelastic dough. In this study reducing agents were added to improve functional properties of sorghum kafirins for bread baking. Study objectives were to determine the effect of reducing agents on protein body structure of sorghum kafirins, investigate the influence on the sorghum batter consistency, and evaluate the effects on the physical characteristics of sorghum bread. Protein analysis, accomplished using RP-HPLC, showed reducing agents, L-cysteine and sodium metabisulfite, reduced protein structure; increasing RP-HPLC total peak area up to 747% and 681%, respectively. Batter consistency was obtained using a RVA. Treatments of L-cysteine (2.5% fwb) expressed increased RVA peak viscosity and decreased final viscosity. Samples treated with sodium metabisulfite (500 ppm fwb) had increased peak viscosity, holding strength and final viscosity. Yeast activity of batter treated with ≥3000 ppm (fwb) sodium metabisulfite caused volume loss of 95% yet at 500 ppm (fwb) sodium metabisulfite did not have an effect. Batter with 2.5% (fwb) L-cysteine experienced reduced yeast activity after 20 min. Sorghum bread characteristics were altered. Loaf volume and crumb grain characteristics of bread produced using sodium metabisulfite (500 ppm) were equal to that of the control, while initial texture and staling were improved. The addition of L-cysteine (2.5% fwb) to breads lowered loaf volume but produced softer initial crumb texture and improved in-vitro protein digestibility by 18.8%.
Keywords: Sorghum; Reducing agents; Gluten-free; Baking; L-cysteine; Sodium metabisulfite; Kafirins